Digital image analysis for the estimation of cracked areas and the soil shrinkage characteristic curve in clay soils amended with composted aewage sludge - Aguilar Torres, M.A.=700 1 De Luna Armenteros, E.; Ordoñez Fernandez, R.
(Es, En)
ilus., 36 ref.
Keywords: ABONOS ORGANICOS; PROPIEDADES FISICO-QUIMICAS SUELO; ESPAÑA; BIOSOLIDOS; ORTORRECTIFICACION